Penggunaan Model Pembelajaran Jigsaw Dapat Meningkatkan Motivasi Dan Hasil Belajar Luas Segi Banyak - Retnowati, Rovyta (Universitas Sebelas Maret, 2020)
In the learning process, the learning model affects students' motivation and learning outcomes. The use of the right learning model makes learning more interesting and not monotonous so that it can improve learning outcomes. The Jigsaw learning model is carried out by discussion in two stages. The first is that students work individually according to the assigned task. And the second with group discussions. The Jigsaw learning model is able to increase motivation and learning outcomes in many ways. The purpose of this study is to increase motivation and learning outcomes in terms of many students of class VI. Based on the analysis and discussion of the research results, it can be concluded that with the Jigsaw learning model there is an increase in motivation and multifaceted learning outcomes in class VI students.